EQUAL PAY FOR EQUAL WORK OR WORK OF EQUAL VALUE: CONCEPT AND APPLICATION - Marković, Velisav; Avramović, Olivera (The European Journal of Applied Economics, 2025)
The Constitution of the Republic of Serbia and legal framework guarantee equal pay for equal work or work of equal value for the employer. Work of equal value refers to work that requires the same level of qualifications, i.e., education, knowledge and skills, in which equal work contribution has been made with equal responsibility. In the paper, the authors, using the normative and comparative law method, deal with the concept, normative structure and implementation of equal pay for equal work or work of equal value principle. It also deals with the term and legal nature of equal pay and work of equal value, as well as the rights to compensation with the key examples of judicial practice.
Keywords: pay, equal pay, equal work, work of equal value